Teacher Experiences, Challenges, and Support Needs in the Implementation of the Philippine MATATAG Curriculum: An Integrative Literature Review - Fuentes, Monajean (Journal of Interdisciplinary Perspectives, 2025)
The Department of Education (DepEd) introduced the MATATAG K to 10 Curriculum to decongest the previous program and enhance foundational skills, digital literacy, and holistic development. Recognizing that its success hinges on the success of basic education teachers, this integrative literature review mapped the initial deployment to identify its scope, teacher-reported challenges, and documented adaptation strategies. Searches were conducted across major academic databases, charting data from 25 sources published between 2020 and 2025, primarily comprising qualitative research on teacher perceptions in the Philippines. Findings consistently identified three significant implementation challenges: insufficient professional development, resource and material constraints, and an increased workload leading to burnout. Teachers primarily addressed these issues through peer collaboration, self-directed learning, and curriculum localization. In conclusion, the literature reveals a significant disconnect between the MATATAG Curriculum’s aspirational policy goals and the systemic support available to educators. This study emphasizes the urgent need for future policy to prioritize comprehensive, sustained, and practical training, alongside adequate resource allocation, to effectively address the implementation gap and the psychological strain experienced by teachers.